Zone Plate Virtual Lenses for Memory-Constrained NLOS Imaging - Luesia-Lahoz, Pablo; Gutierrez, Diego; Muñoz, Adolfo (Jornada de Jóvenes Investigadores del I3A, 2023)
Phasor Fields is a wave-based formulation that allows computing time-efficient NLOS reconstructions using Rayleigh-Sommerfeld diffraction kernels. Unfortunately, these kernels are heavy in memory, hampering the integration in memory-constrained devices. We propose alternative kernels based on zone plates that require 16 times less memory to store, offering an attractive trade-off.